The great American songbooks : musical texts, modernism, and the value of popular culture - Graham, T. Austin (New York : Oxford University Press, 2013)
'The Great American Songbooks' shows how popular music shapes and permeates a host of modernism's hallmark texts. Austin Graham begins his study of 20th-century texts with a discussion of American popular music and literature in the 19th century.
Musical literature, its theory and practice -- Songs not in thy songs: musical forms and American free verse -- The literary soundtrack: F. Scott Fitzgerald's heard and unheard melodies -- Make them black and bid them sing: musical poetics, racial transformation, and the Harlem renaissance -- "Got over": the chorus girl novel and the musical stage -- The bridge: motifs in contemporary musical fiction.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: American literature -- 20th century -- History and criticism; Music in literature; Songbooks, English -- United States -- History and criticism; Popular music -- United States -- History and criticism; Music, Influence of; Sheet music -- United States -- History; Modernism (Literature) -- United States; Littérature américaine -- 20e siècle -- Histoire et critique; Musique dans la littérature.; Musique populaire -- États-Unis -- Histoire et critique; Musique -- Influence; Musique imprimée -- États-Unis -- Histoire; Modernisme (Littérature) -- États-Unis.; LITERARY CRITICISM -- American -- General; American literature; Modernism (Literature); Music in literature; Music, Influence of; Popular music; Sheet music; Songbooks, English; United States; 1900-1999; Criticism, interpretation, etc; History